Reversal of the Kynurenine Pathway of Tryptophan Catabolism May Improve Depression in ART-treated HIV-infected Ugandans - Martinez, Priscilla; Tsai, Alexander C.; Muzoora, Conrad; Kembabazi, Annet; Weiser, Sheri D.; Huang, Yong; Haberer, Jessica E.; Martin, Jeffrey N.; Bangsberg, David R.; Hunt, Peter W. (Journal of acquired immune deficiency syndromes, 2014)
Background: Major depressive disorder is highly prevalent among HIV-infected persons, and depression symptom severity improves during the course of HIV antiretroviral therapy (ART). The potential biologic pathways explaining these phenomena remain unclear. We investigated the extent to which ART-mediated suppression of the kynurenine pathway of tryptophan catabolism (via indoleamine 2,3-dioxygenase-1 and potentially other sources) may correlate with improvements in depression symptom severity in this setting. Method: We used the first year of data from the Uganda AIDS Rural Treatment Outcomes Study, a prospective cohort of 504 HIV-infected individuals initiating their first ART regimen in rural Uganda. We fitted random-effects regression models to estimate the associations between plasma tryptophan, plasma kynurenine, dietary diversity, and self-reported depression symptom severity. Results: Greater depressive symptoms were associated with both lower plasma tryptophan and higher plasma kynurenine/tryptophan (KT) ratio over 12-month follow-up. In multivariable adjusted models, declines in KT ratio and increases in plasma tryptophan levels partially explained ART-mediated improvements in depressive symptom severity. The association between KT ratio and depression symptom severity was stronger among persons with protein-deficient diets than among those with protein-rich diets. Conclusions:IDO-mediated tryptophan catabolism may contribute to depression symptom severity among HIV-infected individuals, particularly among those with poor dietary protein intake. ART-mediated improvements in depressive symptom severity may also be at least partially mediated by immunologic mechanisms. Interventions to reduce immune activation, and dietary protein supplementation, may be promising strategies to further reduce depression in this setting
Keywords: Tryptophan Catabolism; Depression in ART; HIV; ART-mediated suppression